2021
DOI: 10.1186/s12887-021-03025-z
|View full text |Cite|
|
Sign up to set email alerts
|

Fluid handling and blood flow patterns in neonatal respiratory distress syndrome versus transient tachypnea: a pilot study

Abstract: Background Cardiovascular and renal adaptation in neonates with Respiratory Distress Syndrome (RDS) and Transient Tachypnea of the Newborn (TTN) may be different. Methods Neonates ≥32 weeks were diagnosed with RDS or TTN based on clinical, radiologic and lung sonographic criteria. Weight loss, feeding, urine output, and sodium levels were recorded for the first 3 days, and serial ultrasounds assessed central and organ Doppler blood flow. A linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The relevant literature has pointed out that the sensitivity and accuracy of lung ultrasound in the diagnosis of pneumothorax are 96.2% and 99.5%, respectively, while the sensitivity and accuracy of chest X-ray diagnosis are 73.1% and 96.5%, respectively. The results showed that the sensitivity of chest X-ray in the diagnosis of pneumothorax is relatively poor [ 27 ]. Aafreen S et al evaluated the diagnostic accuracy of bedside lung ultrasound and chest X-ray in patients with suspected pneumonia through prospective clinical studies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relevant literature has pointed out that the sensitivity and accuracy of lung ultrasound in the diagnosis of pneumothorax are 96.2% and 99.5%, respectively, while the sensitivity and accuracy of chest X-ray diagnosis are 73.1% and 96.5%, respectively. The results showed that the sensitivity of chest X-ray in the diagnosis of pneumothorax is relatively poor [ 27 ]. Aafreen S et al evaluated the diagnostic accuracy of bedside lung ultrasound and chest X-ray in patients with suspected pneumonia through prospective clinical studies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], it has been noticed that the author names have been captured incorrectly. The given and family names were interchanged.…”
mentioning
confidence: 99%